Ensuring Economic Security of Russia and Eurasian Countries as an Imperative of Effective Eurasian Integration - A.A, Krylov; S.A, Pobyvayev; A.I, Selivanov; S.N, Silvestrov; V.G., Starovoitov; D.V, Troshin (International Journal of Engineering and Technology, 2018)
The task of the authors was to identify the role of country economic security in the Eurasian integration. To this end, the approaches to economic security in Europe, Russia and Asian countries are analyzed. The differences in the systems of national economic security and in the key approaches to its provision are primarily due to the historically established internal economic and geo-economic conditions. There is a fairly wide range of paradigms of national economic security, primarily the differences between the European approaches and the approach of Russia. Information on the state, principles and mechanisms of organization of national economic security systems in Asian countries is practically absent in Russian science. It was also necessary to analyze the typology of threats in order to clarify the prospects of integration of national economic security systems. The authors substantiate the position that ensuring national economic security is an important imperative of integration and development in the Eurasian space, competitiveness and economic sovereignty of countries. The article systematically organizes the facts about the types of organization of national economic security, explains the need for the countries of Eurasia active system of economic security as a response to the challenges of our time. The authors formulate the basic principles of Eurasian integration in the field of national security, involving both sovereignty and harmonization of national systems aimed at protecting economic interests.Â Â Â